Dental age estimation by different methods in patients with amelogenesis imperfecta. (May 2019) - Kirzioglu, Zuhal; Ceyhan, Derya; Bayraktar, Canan
Highlights: Amelogenesis imperfecta did not present an impact on the dental age. Haavikko's and Nolla's methods were more accurate in the dental age estimation compared to the Demirjian's method. Dental age estimation studies comprising other defects affecting the tooth structure and morphology are also necessary. Abstract: Amelogenesis imperfecta (AI) is one of the developmental enamel defects. In patients with AI, as well as enamel defects, some dental anomalies are encountered and may affect tooth development. For children whose enamel structure is not normal, whether an accurate result can be obtained by dental age determination methods is not clear. The aims of this study are to determine the dental age for the assessment of tooth development in patients with AI by 3 different methods, to decide a method that will present the most accurate result to the chronological age, and to build a basis in terms of postmortem identification. The records of patients who were referred to the Department of Pediatric Dentistry between the years of 1999 and 2018, and diagnosed with AI were reviewed. At the age of 6–15 years, 58 patients (33 males–25 females) (Group I) with AI were determined. A total of 116 healthy individuals (66 males–50 females) (Group II) who were age and gender matched with the AI group were selected as the control group. Chronological age was calculated, and Nolla's, Demirjian's and Haavikko's methods were used to estimate dental age. Chronological and dental ages were compared according to the group and gender. The accuracy of three methods was also evaluated. There was no statistical significant differences for the tooth development in terms of group and gender. Dental age was over-estimated by Demirjian's method and under-estimated by Nolla's and Haavikko's methods. Haavikko's and Nolla's methods were more accurate in the dental age estimation. AI did not present an impact on the dental development. By using particularly Haavikko's method, the possible margin of error in evaluations of dental development can be reduced. Similar studies comprising other defects affecting the tooth structure and morphology are also necessary.